Gene Flow Risks From Transgenic Herbicide-Tolerant Crops to Their Wild Relatives Can Be Mitigated by Utilizing Alien Chromosomes - Song, Xiaoling; Yan, Jing; Zhang, Yuchi; Li, Hewei; Zheng, Aiqin; Zhang, Qingling; Wang, Jian; Bian, Qing; Shao, Zicheng; Wang, Yu; Qiang, Sheng (Frontiers in Plant Science, 2021)
Transgene insertions into the A or C genomes of oilseed rape (AACC, 2n = 38) may affect their gene flow to wild relatives like Brassica juncea (AABB, 2n = 36). However, further evidence is required for this and the inherent mechanisms of reproductive incompatibility. Here, during herbicide selections, the first-to fourth-generation progenies of a B. juncea × glyphosate-tolerant oilseed rape cross [EPSPS-gene insertion in the A-genome (Roundup Ready, event RT73)], were found to have higher fitness than a B. juncea × glufosinate-tolerant oilseed rape cross [PAT-gene insertion in the C-genome (Liberty Link, event HCN28)]. Karyotyping and Bacterial artificial chromosome- Fluorescence in situ hybridization (BAC-FISH) analyses showed that crossed progenies of the EPSPS and PAT transgenic cultivars with wild B. juncea were mixoploids, and their genomes converged over four generations to 2n = 36 (AABB) and 2n = 37 (AABB + C), respectively. Chromosome pairing of pollen mother cells was more irregular in the PAT progenies than EPSPS, and the latter lost their C-genomes faster. Thus, transgene insertions into the different genomes of B. napus affects introgression during herbicide selection. This suggests that gene flow from transgenic crops to wild relatives could be mitigated by breeding transgenic allopolyploid crops, where the transgene is inserted into an allo-genome.